URGENSI NASKAH AKADEMIK DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN YANG BAIK - Delfina Gusman (Faculty of Law, Universitas Diponegoro, 2011)
The Academic Manuscript of Law has important value in forming of good law and regulation, so that its existence has to be considered to be requirement. The making of Academic Manuscript of Law begins with research so that the resulting rules can be accepted by communities. Strengthening the position of academic manuscript of law is necessary to emphasize in the revisions Law on establishment of legislation.